2017
DOI: 10.3382/ps/pew184
|View full text |Cite
|
Sign up to set email alerts
|

A slope-ratio precision-fed rooster assay for determination of relative metabolizable energy values for fats and oils

Abstract: The precision-fed rooster assay (PFRA) frequently yields TME values for fats and oils in excess of their gross energies. Six experiments were conducted to determine if the PFRA could be combined with a slope-ratio type assay to yield more useful lipid TME values. In experiment (EXP) 1, refined corn oil (RCO) was fed to conventional and cecectomized roosters at zero, 5, 10, 15, and 20% of a ground corn diet. In EXP 2 through 6, lipids were fed to conventional roosters at zero, 5, and 10% in a ground corn diet. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
3
8
0
Order By: Relevance
“…The available information, together with the results of the current research, suggest that within practical levels of use, the beneficial effects of fat on nutrient retention increase as the level of supplemental fat increases. Similar, results have been reported recently by Aardsma and Parsons (2016).…”
Section: Coefficient Of Total Tract Apparent Retention and Ame Of Thesupporting
confidence: 93%
See 4 more Smart Citations
“…The available information, together with the results of the current research, suggest that within practical levels of use, the beneficial effects of fat on nutrient retention increase as the level of supplemental fat increases. Similar, results have been reported recently by Aardsma and Parsons (2016).…”
Section: Coefficient Of Total Tract Apparent Retention and Ame Of Thesupporting
confidence: 93%
“…In this respect, Vieira et al (2002) and Peña et al (2014) reported in broilers that the AME of the experimental ASO source increased by 2.53 and 5.36 MJ/kg, when the level of the oil in the diet increased from 40 to 80 g/kg or from 20 to 60 g/kg, respectively. Aardsma and Parsons (2016) reported also that the TME of SO and maize oil increased by 1.01 and 2.33 MJ/kg, as the level of oil supplementation increased from 50 to 100 g/kg.…”
Section: Coefficient Of Total Tract Apparent Retention and Ame Of Thementioning
confidence: 86%
See 3 more Smart Citations